Biomass Yield, Chemical Composition and In Vitro Gas Production of Different Dhaincha (Sesbania spp.) Accessions from Bangladesh - Kabir, A. K. M. Ahsan; Moniruzzaman, M; Gulshan, Zubaida; Rahman, A. B. M. Mustanur; Sarwar, A. K. M. Golam (Indian Journal of Animal Nutrition, 2018)
This study was carried out to characterize the dhaincha germplasms based on biomass yield and nutritional quality, and to assess their suitability as animal feed by an in vitro analysis. A field experiment was conducted following complete randomized design in 3×2 m2 plot at the spacing of 50cm × 15 cm (row-row × plant-plant) at Field Laboratory of the Department of Crop Botany, Bangladesh Agricultural University. Biomass yield and related data were collected at the seedling (35 days after sowing) and maturity stages. The nutritional quality and in vitro gas production were accomplished from 35 days old dhaincha samples following standard procedure. In both seedling and mature stages, wide and significant differences were observed in biomass yield and other morphological descriptors among the studied dhaincha accessions. The highest ash content (9.82%) was produced in Rangpur region and the lowest (6.74%) in Gaibandha region. Crude protein content varied from 16% to 24% and crude fibre content from 14% to 16%. The maximum nitrogen free extract value (>41%) was found in Khulna and Gaibandha region. The in vitro gas production was varied from 17% to 23%. The total gas production (V08+V24) was highest in Khulna region and lowest in Gaibandha region. Organic dry matter digestibility and metabolizable energy value were greater in Sirajganj region and fewer in Rangpur region. It could be concluded that a wide regional variation was observed among the collected dhaincha accessions. The nutritional quality of dhainchaaccessions from Khulna region was better than that of other regions; it can be used as rich source of feed ingredient in animal diet.This study was carried out to characterize the dhaincha germplasms based on biomass yield and nutritional quality, and to assess their suitability as animal feed by an in vitro analysis. A field experiment was conducted following complete randomized design in 3×2 m2 plot at the spacing of 50cm × 15 cm (row-row × plant-plant) at Field Laboratory of the Department of Crop Botany, Bangladesh Agricultural University. Biomass yield and related data were collected at the seedling (35 days after sowing) and maturity stages. The nutritional quality and in vitro gas production were accomplished from 35 days old dhaincha samples following standard procedure. In both seedling and mature stages, wide and significant differences were observed in biomass yield and other morphological descriptors among the studied dhaincha accessions. The highest ash content (9.82%) was produced in Rangpur region and the lowest (6.74%) in Gaibandha region. Crude protein content varied from 16% to 24% and crude fibre content from 14% to 16%. The maximum nitrogen free extract value (>41%) was found in Khulna and Gaibandha region. The in vitro gas production was varied from 17% to 23%. The total gas production (V08+V24) was highest in Khulna region and lowest in Gaibandha region. Organic dry matter digestibility and metabolizable energy value were greater in Sirajganj region and fewer in Rangpur region. It could be concluded that a wide regional variation was observed among the collected dhaincha accessions. The nutritional quality of dhaincha accessions from Khulna region was better than that of other regions; it can be used as rich source of feed ingredient in animal diet.